Evaluasi tingkat keasinan relatif dan profil sensori garam rumput laut menggunakan metode magnitude estimation dan rate-all-that-apply (RATA): Evaluation of relative saltiness level and sensory profile of seaweed salt using magnitude estimation and Rate-All-That-Apply (RATA) - Anggrei Viona Seulalae; Endang Prangdimurti; Dede Robiatul Adawiyah; Nurjanah Nurjanah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
Hypertension is a silent killer disease, with the highest mortality rate in Indonesia. The high risk of developing this disease is caused by an unhealthy lifestyle, one of which is excessive consumption of salt/sodium. Seaweed salt is an alternative to low-sodium salt that can be consumed by people with hypertension. Sensory parameters, especially the level of saltiness and sensory profiles, are important for the future development of seaweed salt. This study aimed to determine the relative saltiness level and sensory profile of seaweed salt by using a consumer-based method. This study consisted of seaweed preparation, seaweed salt Sargassum polycystum, and Ulva lactuca production and evaluation of relative saltiness using the magnitude estimation (ME) method and sensory profile using the rate-all-that-apply (RATA) method. Data were analyzed using an independent sample t-test with a 95% confidence level. The results showed that seaweed salt S. polycystum and U. lactuca had NaCl levels of 43.77±0.54% and 18.98±0.29%. The relative saltiness of the seaweed salt solution was lower than the NaCl 0.54% solution, a higher concentration was needed to provide the same stimulus as the 0.54% NaCl solution. The seaweed salt S. polycystum solution felt a salty taste stimulus equivalent to the 0.54% NaCl solution at a concentration of 0.85% and U. lactuca at a concentration of 0.89%. Seaweed salt has the dominant sensory attributes of being salty, umami, bitter, and eggy. S. polycystum salt has a more neutral and preferred sensory profile.